LHX6 is a sensitive methylation marker in head and neck carcinomas - Estecio, M. R. H.; Youssef, E. M.; Rahal, Paula [UNESP]; Fukuyama, E. E.; Gois-Filho, J. F.; Maniglia, J. V.; Goloni-Bertollo, E. M.; Issa, J-P J.; Tajara, E. H. (Nature Publishing Group, 2006)
Head and neck cancer remains a morbid and often fatal disease and at the present time few effective molecular markers have been identified. The purpose of the present work was to identify new molecular markers for head and neck squamous cell carcinoma (HNSCC). We applied methylation-sensitive arbitrarily primed PCR (MS/APPCR) to isolate sequences differentially methylated in HNSCC. The most frequently hypermethylated fragment we found maps close to a cytosine guanine dinucleotide (CpG) island on chromosome 9q33.2, and hypermethylation of this CpG island was associated with transcriptional silencing of an alternative transcript of the LHX6 gene. Using combined bisulfite restriction analysis (COBRA), hypermethylation of this fragment was detected in 13 of 14 (92.8%) HNSCC cell lines studied and 21 of 32 (65.6%) primary tumors, whereas little or no methylation was seen in 10 normal oral mucosa samples. We extended this investigation to other cancer cell lines and methylation was found in those derived from colon, breast, leukemia and lung, and methylation was also found in 12/14 primary colon tumors. These findings suggest that differentially methylated (DIME)-6 hypermethylation is a good cancer marker in HNSCC as well as in other kinds of neoplasias and confirm the importance of searching for markers of epigenetic dysregulation in cancer.
Keywords: DNA methylation; head and neck cancer; solid tumors; early diagnosis; circulating DNA